Leben am Ochsenweg – die völkerwanderungszeitliche Siedlung von Kropp - Maaß, Alexander (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
Between April 2023 and January 2024, a development-lead archaeological excavation was conducted at the northern edge of Kropp municipality in Schleswig-Holstein. The excavation aimed to investigate numerous findings indicating a large settlement from the Migration Period, covering anarea of 7.5 hectares. The very well-preserved remains revealed a one-phase Haufendorf (clustered village) with detailed insights into its structure and organization, including the central area and surrounding farmsteads. The settlement featured twelve main farmsteads, each with longhouses, enclosures, and specialized buildings, some with unique functions suggesting social or ritual significance. Notable findings include well-preserved building plans of longhouses with internal divisions, wagon traces, and evidence of possible ritual activities such as sacrificial offerings.The settlement appears to have been intentionally abandoned and burned after a short period of occupation, likely due to environmental factors like groundwater levels. The excellent preservation conditions provided valuable information on the socio-economic and spiritual aspects of early medieval rural life, offering a rare comprehensive view of a 5thcentury AD village in Schleswig-Holstein.